2018
DOI: 10.1038/s41386-018-0235-1
|View full text |Cite
|
Sign up to set email alerts
|

Drug-taking in a socio-sexual context enhances vulnerability for addiction in male rats

Abstract: Vulnerability to develop addiction is influenced by numerous factors, including social behavior. Specifically, in human users, drug taking in a socio-sexual context appears to enhance further drug-seeking behavior. Users report heightened sexual pleasure as a motivation for further drug use and display risk behaviors even when tested in drug-free state. Here, using a preclinical model of limited voluntary drug use in rats, the hypothesis was tested that methamphetamine (Meth)-taking concurrently with socio-sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 55 publications
(75 reference statements)
4
13
0
Order By: Relevance
“…Results fit with the overall framework that mPFC is involved in formation and consolidation of context-response associations, including a role for ACA in working memory for response-outcome associations (Kesner and Churchwell, 2011). Here, findings support a role for ACA in forming associations between an intrinsic context of Meth exposure while engaging in emotional reward behavior, which in this study consisted of sexual reward behavior (see Kuiper et al (2019) for additional detailed discussion). Studies have also shown that inactivation of mPFC immediately after a learning task causes memory impairments (Carballo-Marquez et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Results fit with the overall framework that mPFC is involved in formation and consolidation of context-response associations, including a role for ACA in working memory for response-outcome associations (Kesner and Churchwell, 2011). Here, findings support a role for ACA in forming associations between an intrinsic context of Meth exposure while engaging in emotional reward behavior, which in this study consisted of sexual reward behavior (see Kuiper et al (2019) for additional detailed discussion). Studies have also shown that inactivation of mPFC immediately after a learning task causes memory impairments (Carballo-Marquez et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…CNO was not administered during the remainder of the experiment (Figure 3B), hence any differences between the CNO and vehicle concurrent groups were the result of inhibition of ACA CaMKII cells during the concurrent Meth and sex exposure and were not caused by differences in prior Meth taking or sex experience. Replicating previous findings (Kuiper et al, 2019), the vehicletreated concurrent group responded more on the active lever than the vehicle non-concurrent group during session 1 of extinction training [t (14) = 1.7, p = 0.045] and both concurrent groups responded more on the active lever than vehicle nonconcurrent males during session 2 of extinction training [t (14) = 1.7, p = 0.020-0.025]. However, prior CNO treatment had no effect on this enhanced drug-seeking behavior as vehicle and CNO-pretreated concurrent males did not differ ( Figure 3D; see Table S6 for all statistical analyses).…”
Section: Chemogenetic Inactivation Of Aca Prevents Effects Of Concurrsupporting
confidence: 88%
See 3 more Smart Citations